Can Educational Policy Influence Major Choices in Higher Education Through Changes in School Curriculum? - Sendzik, Norbert; Erdmann, Melinda; Helbig, Marcel (Social inclusion, 2025)
The impact of high school curriculum reforms on students’ major choices in higher education remains an underexplored field, despite their potential role in shaping workforce composition, economic development, and social mobility. This study addresses this gap by examining the varying emphasis on compulsory school subjects across German states. We focus on non‐core subjects that vary significantly in importance across states (civic education) or that are part of the curriculum in some states but not in others (economics and computer science). These subjects are increasingly recognized as essential for fostering democratic values, economic understanding, and digital literacy, which also shape students’ career aspirations and educational trajectories, ultimately contributing to a skilled workforce and potentially reducing the shortage of skilled labor. Using a novel dataset documenting state‐specific introduction of compulsory courses and instructional time from 1995 to 2018, we analyze their influence on major choice. This dataset is linked with German higher education register data to assess whether increased compulsory instruction time and the introduction of compulsory courses affect students’ subsequent major choices. For our analyses, we employed two‐way fixed effects models to examine whether changes in the curriculum led to changes in major choices. Our results indicate small but positive effects of additional compulsory hours in civic education and economics on related major choices. However, our findings for computer science courses remain inconclusive. These results, along with the methodological limitations identified, highlight the need for further research on the long‐term educational implications of school curriculum reforms.